Ethics of Using AI in Academics: A Case Study Among Informatics Students at Citra Bangsa University - Toulay, Yulce Getruida; Sogen, Maria Magdalena Beatrice; Leo, Agni Duariti; Ndun, Sandro William (JUPE : Jurnal Pendidikan Mandala, 2025)
The advancement of Artificial Intelligence (AI) has penetrated the academic field, offering ease in learning processes and task completion. However, ethical concerns regarding its use arise. This study aims to analyze the awareness and ethical perspective of Informatics students at Universitas Citra Bangsa towards AI usage. A total of 30 students from semesters 2, 4, and 6 participated by filling out a questionnaire. The results show a high level of interest in using AI tools responsibly and a strong demand for formal ethical guidance from the university. The research concludes that ethical education related to AI is essential and should be integrated into the academic curriculum.